(untitled) (Journal of Naval Architecture and Marine Engineering, 2023)
In this take a glance at, we have a tendency to investigated the results of hydrodynamics (MHD) Casson and Carreau fluid (CCF) heat via a porous medium at the aspect of a stretching sheet. Variable thermal physical phenomenon and suction/injection parameter results are also taken into the thought. Similarity modifications area unit applied to convert the governing equations of the CCF glide model into dimensionless non-linear normal differential equations. The answers area unit conferred through graphs and tabular type. the velocity, concentration, temperature profile, skin friction constant, and also the Nusselt and Sherwood numbers below the result of various parameters area unit studied. The fluid waft is analyzed for every suction and injection cases. From the analysis finished, it’s miles discovered that the speed profile reduces via increasing the magnetic parameter. The temperature space enhances by increasing the variable thermal physical phenomenon and also the Nusselt wide selection reveals opposite behaviour